Gdańsk- Wrzeszcz Aleja Grunwaldzka / fot. A. Zborski. - Zborski, Andrzej (1929-2017) (Biuro Wydawnicze "RUCH", 1960)
Przedstawia bloki przy Al. Grunwaldzkiej we Wrzeszczu, w pobliżu Domu Towarowego "Neptun", ok. 1970 r.